Mooring effect on wave frequency response of round shape FPSO - Siow, C. L. (Penerbit UTM Press, 2015)
This paper presents the motions response of moored Round Shape FPSO model due to the wave effect. The proposed of this research is analyzed the possibility of model motion response affected by different mooring system attach to the model. Model experiment was applied in this research to collect motion data for the study. Besides, the numerical simulation using diffraction potential, diffraction potential with Morison Heave correction and ANSYS frequency domain study were also applied in this research to generate comparative data to the experimental results. To investigate the effect of the mooring system to motion response, the model experiment was firstly conducted by attached model scale catenary mooring lines to Round Shape FPSO model. After that, the experiment was repeated by attached model scale taut mooring lines to the same model. The results obtain from the regular wave experiment tests and numerical simulation test were presented in this paper. This research concluded that the mooring systems would not give significant effect to wave frequency motion response after compared the motion result obtain from model experiment conducted using different mooring system.